Digital Storytelling as a Tool for Multicultural Awareness in English Language Learning - Mele Moa; Pati Falani; Faafaite Matanitobua (International Journal of Language and Ubiquitous Learning, 2026)
The increasing cultural diversity in English language classrooms has emphasized the importance of developing multicultural awareness as part of communicative competence. Traditional pedagogical approaches often fail to provide learners with meaningful opportunities to explore cultural identities and perspectives. Digital storytelling (DST) has emerged as a pedagogical tool that integrates language learning with intercultural understanding through narrative creation, visual expression, and reflective engagement. This study investigates the effectiveness of digital storytelling in fostering multicultural awareness and improving English language proficiency among learners in multilingual and multicultural contexts. A mixed-methods research design was adopted, combining quantitative and qualitative approaches to obtain a holistic understanding of learners’ linguistic and intercultural development. The participants consisted of 90 undergraduate English language learners from three universities in Indonesia, divided into experimental (DST-based instruction) and control (traditional instruction) groups. Quantitative data were collected through pre- and post-tests measuring intercultural sensitivity and language performance, while qualitative data were gathered from reflective journals and focus group interviews. Statistical analysis using paired-sample t-tests revealed significant improvement in the experimental group’s intercultural awareness (p < 0.01) and oral fluency (p < 0.05). Qualitative findings indicated that storytelling enhanced empathy, respect for diversity, and critical reflection on cultural values. The study concludes that digital storytelling serves as an effective pedagogical medium for integrating multicultural education into English language learning. It not only enhances linguistic competence but also promotes intercultural dialogue and inclusivity. The findings underscore the transformative role of narrative-based digital pedagogy in preparing learners for global citizenship and multicultural communication.